The Effect of Investor Inattention on non-GAAP Disclosure - Basu, Riddha; Pierce, Spencer R.; Stephan, Andrew (The Accounting Review, 2022)
We examine whether investor inattention influences managers’ non-GAAP earnings disclosures. Hirshleifer and Teoh’s (2003) theoretical model predicts that managers are more likely to disclose upwardly-biased non-GAAP metrics when investors are inattentive. Employing a measure that captures exogenous variation in institutional investor inattention, we find that managers are more likely to provide non-GAAP disclosures, particularly those where non-GAAP earnings are greater than GAAP earnings, when inattention is high. Moreover, inattention is positively associated with the magnitude of non-GAAP exclusions, which suggests managers present better non-GAAP performance to inattentive investors. Consistent with managers exploiting investors’ limited attention, we find that stock prices respond more strongly to non-GAAP exclusions when investors are inattentive and that managers are more likely to respond to inattention with income increasing non-GAAP disclosures if they sell shares following the disclosure. Taken together, these findings suggest that managers respond opportunistically to inattentive institutions by disclosing aggressive non-GAAP earnings metrics.